Design Modifications of a Thin Wall Part from Aluminium to Magnesium - Samekto, Haryanti (International Journal of Integrated Engineering, 2010)
Design and materials can not be independently decided. In this study, design modifications of a thin wall part were made as a consequence of material change. A fishing reel spool was made from Aluminium and it would be change to Magnesium. Two modifications were carried out i.e. wall thickness increase and ribs addition. Finite element method was applied to optimize the design under static and dynamic loading according to the operation condition of the spool. Finite element analysis results confirmed that increasing the wall thickness was sufficient for radial compression force. As the wall thickness of Al spool was 0.65 mm, the wall thickness of Mg spool was increased to 1 mm to obtain equivalent factor of safety. From the analysis results, increasing thickness was considered not sufficient to stand torsion loading in Mg spool, therefore ribs and outer ring was added to enhance the wall integrity